Harmful influence of "fashionable" diets on the state of health of students - Gorobey M.P. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2012)
The analysis of data of modern scientific literature is conducted on issue of feed of students. It is shown that most students have erroneous enough presentations in relation to a healthy feed, does not hold his requirements and does not consider it harmful. Negative influence of "fashionable" diets and inefficient feed on metabolism of organism and state of health of student young people is exposed. The necessity of abandonment from the "fashionable" diets of feed, which are insalubrious students is well-proven. It is set that an observance of requirements of the balanced feed is a correct choice for the prophylaxis of illnesses strengthening of the state of health of students. The ways of healthy feed are offered for the improvement of the state of health of student young people.